2021
DOI: 10.1590/0103-8478cr20200677
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors that affect tick infestation in Nelore x Angus crossbreed cattle

Abstract: This study evaluated the effects of seasons and latitude on tick counting and determined the best model to estimate genetic parameters for tick count and hair coat. Records of animals naturally exposed to ticks on farms in several Brazilian states and in Paraguay were used. The ANOVA was used to verify the effects of seasons and latitude on the tick count trait. Spring was the season with the highest average, followed by summer and autumn, which showed no differences between them. The winter presented the lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, the genetic resistance of cattle to tick infestation and tick-induced diseases seems to be more dependent on skin immune responses and abundance of tick-resistant genes [19]. In a recent study, Feltes et al [20] reported a very low genetic correlation between tick count and haircoat characteristics in a population of crossbred Angus x Nelore, which suggests that these traits are regulated by different genes.…”
Section: Physical Properties Of Haircoatsmentioning
confidence: 99%
“…However, the genetic resistance of cattle to tick infestation and tick-induced diseases seems to be more dependent on skin immune responses and abundance of tick-resistant genes [19]. In a recent study, Feltes et al [20] reported a very low genetic correlation between tick count and haircoat characteristics in a population of crossbred Angus x Nelore, which suggests that these traits are regulated by different genes.…”
Section: Physical Properties Of Haircoatsmentioning
confidence: 99%